Retinal Anatomy of the New Zealand Kiwi: Structural Traits Consistent With Their Nocturnal Behavior. Issue 4 (5th November 2014) - Corfield, Jeremy R.; Parsons, Stuart; Harimoto, Yoshitetsu; Acosta, Monica L.
ABSTRACT: Kiwi ( Apteryx spp.) have a visual system unlike that of other nocturnal birds, and have specializations to their auditory, olfactory, and tactile systems. Eye size, binocular visual fields and visual brain centers in kiwi are proportionally the smallest yet recorded among birds. Given the many unique features of the kiwi visual system, we examined the laminar organization of the kiwi retina to determine if they evolved increased light sensitivity with a shift to a nocturnal niche or if they retained features of their diurnal ancestor. The laminar organization of the kiwi retina was consistent with an ability to detect low light levels similar to that of other nocturnal species. In particular, the retina appeared to have a high proportion of rod photoreceptors as compared to diurnal species, as evidenced by a thick outer nuclear layer, and also numerous thin photoreceptor segments intercalated among the conical shaped cone photoreceptor inner segments. Therefore, the retinal structure of kiwi was consistent with increased light sensitivity, although other features of the visual system, such as eye size, suggest a reduced reliance on vision. The unique combination of a nocturnal retina and smaller than expected eye size, binocular visual fields, and brain regions make the kiwi visual system unlike that of any bird examined to date. Whether these features of their visual system are an evolutionary design that meets their specific visual needs or are a remnant of a kiwi ancestor that relied more heavily on vision is yet to be determined. Anat Rec, 298:771–779, 2015. © 2014 Wiley Periodicals, Inc.